2017
DOI: 10.1016/j.immuni.2017.06.021
|View full text |Cite
|
Sign up to set email alerts
|

Local Modulation of Antigen-Presenting Cell Development after Resolution of Pneumonia Induces Long-Term Susceptibility to Secondary Infections

Abstract: Lung infections cause prolonged immune alterations and elevated susceptibility to secondary pneumonia. We found that, after resolution of primary viral or bacterial pneumonia, dendritic cells (DC), and macrophages exhibited poor antigen-presentation capacity and secretion of immunogenic cytokines. Development of these "paralyzed" DCs and macrophages depended on the immunosuppressive microenvironment established upon resolution of primary infection, which involved regulatory T (Treg) cells and the cytokine TGF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
146
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(150 citation statements)
references
References 62 publications
4
146
0
Order By: Relevance
“…However, very few studies have investigated the post-acute long-term effects of systemic inflammation on NK cells and their cell intrinsic activities independent of the immune environment. A recent report suggested that NK cell responsiveness was intact 7 days after bacterial and viral pneumonia, but their activation during secondary infection was hampered by the immunosuppressive environment in the lungs (34). These results are similar to what we present here, where 2-9 weeks after endotoxemia, the environment restricts NK cell activation during re-stimulation, independently of their cell-intrinsic functions.…”
Section: Discussionsupporting
confidence: 91%
“…However, very few studies have investigated the post-acute long-term effects of systemic inflammation on NK cells and their cell intrinsic activities independent of the immune environment. A recent report suggested that NK cell responsiveness was intact 7 days after bacterial and viral pneumonia, but their activation during secondary infection was hampered by the immunosuppressive environment in the lungs (34). These results are similar to what we present here, where 2-9 weeks after endotoxemia, the environment restricts NK cell activation during re-stimulation, independently of their cell-intrinsic functions.…”
Section: Discussionsupporting
confidence: 91%
“…However, few studies have investigated the post-acute longterm effects of systemic inflammation on NK cells and their cellintrinsic activities independent of the immune environment. A recent report suggested that NK cell responsiveness was intact 7 days after bacterial and viral pneumonia, but activation during secondary infection was hampered by the immunosuppressive environment in the lungs (Roquilly et al, 2017). These results are similar to what we present here, where 2-9 weeks after endotoxemia, the environment restricts NK cell activation during re-stimulation, independently of their cell-intrinsic functions.…”
Section: Discussionsupporting
confidence: 91%
“…The protective effect of FLT3L was observed even after the adoptive transfer of DCs treated with FLT3L into the septic animals [189]. Intrapulmonary transfer of bone marrow-derived DCs (BMDCs) also prevented the development of fatal pulmonary aspergillosis in mice recovering from sepsis [190]. Animals recovering from sepsis are more prone to develop severe secondary infections due to prolonged immunosuppression via mechanisms involving transforming growth factor β (TGF-β) secreted by paralyzed DCs causing accumulation of regulatory T cells (Tregs) in lungs and the development of tolerogenic DCs expressing Blimp1 [191].…”
Section: Dendritic Cells (Dcs) and Tlr Expressionmentioning
confidence: 99%